A Catalyst toward Sustainability? Exploring Social Learning and Social Differentiation Approaches with the Agricultural Poor - Shaw, Alison; Kristjanson, Patricia M. (MDPI, 2014)
Emerging sustainability challenges, such as food security, livelihood development and climate change, require innovative and experimental ways of linking science, policy and practice at all scales. This requires the development of processes that integrate diverse knowledge to generate adaptive development strategies into the future. Social learning is emerging as a promising way to make these linkages. If and how social learning approaches are being applied in practice among smallholder farming families—the bulk of the world’s food producers, requires specific attention. In this paper we use a case study approach to explore social learning among the agricultural poor. Five key evaluative factors: context assessment, inclusive design and management, facilitating learning, mobilizing knowledge and assessing outcomes, are used to analyze nine projects and programs in (or affiliated with) the Consultative Group on International Agricultural Research (CGIAR). We explore three main questions: (1) in what contexts and in what ways are socially differentiated and marginalized groups enrolled in the learning process? (2) what, if any, are the additional benefits to social learning when explicitly using strategies to include socially differentiated groups? and (3) what are the benefits and trade-offs of applying these approaches for development outcomes? The findings suggest that, in the agricultural development context, social learning projects that include socially differentiated groups and create conditions for substantive two-way learning enhance the relevance and legitimacy of knowledge and governance outcomes, increasing the potential for accelerating sustainable development outcomes.